Poverty and children's adjustment - Luthar, Suniya S. (Sage Publications, 1999)
Poverty and Children's Adjustment gives an interdisciplinary perspective on the effects of poverty, lack of education, and other negative socioeconomic forces on children's development. This volume provides an in-depth review of the literature on psychopathology among children faced with sociodemographic disadvantage, as well as suggested directions for future research. Suniya S.
Keywords: Poor children -- United States -- Psychology.; Children with social disabilities -- United States -- Psychology.; Poverty -- United States -- Psychological aspects.; Adjustment (Psychology) in children -- United States.; Child psychopathology -- United States.; Social adjustment.; Adaptability (Psychology); Children.; Poverty.; Social Adjustment; Adaptation, Psychological; Child; Poverty; Enfants pauvres -- États-Unis -- Psychologie.; Enfants socialement défavorisés -- États-Unis -- Psychologie.; Pauvreté -- États-Unis -- Aspect psychologique.; Ajustement chez l'enfant -- États-Unis.; Enfants -- Psychopathologie -- États-Unis.; Adaptation sociale.; Adaptation (Psychologie); Enfants.; Pauvreté.; children (people by age group); poverty.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; Social adjustment; Children; Adjustment (Psychology) in children; Child psychopathology; Children with social disabilities -- Psychology; Poor children -- Psychology; Poverty -- Psychological aspects; United States; Armut; Kind; Integration; Unterprivilegierung; USA